COVID-19: Safe Guidelines for Breast Imaging During the Pandemic. Issue 4 (November 2020) - Seely, Jean M.; Scaranelo, Anabel M.; Yong-Hing, Charlotte; Appavoo, Shusheila; Flegg, Carolyn; Kulkarni, Supriya; Kornecki, Anat; Wadden, Nancy; Loisel, Yves; Schofield, Stephanie; Leslie, Sandra; Gordon, Paula
During the COVID-19 pandemic, breast imaging must be performed using safe practices. Balancing the need to avoid delays in the diagnosis of breast cancer while avoiding infection requires careful attention to personal protective equipment and physical distancing and vigilance to maintain these practices. The Canadian Society of Breast Imaging/Canadian Association of Radiologists guideline for breast imaging during COVID-19 is provided based on priority according to risk of breast cancer and impact of delaying treatment. A review of the best practices is presented that allow breast imaging during COVID-19 to maximize protection of patients, technologists, residents, fellows, and radiologists and minimize spread of the infection. The collateral damage of delaying diagnosis of breast cancer due to COVID-19 should be avoided when possible.